A study of inter-generational differences in personal values of the chinese managers in Singapore. - Saik, Hwai Choo. (2008)
In this project, we took a look into the differences in personal value systems of the Chinese managers in Singapore across different generations. Our findings for measures developed with both Eastern and Western constructs generally supports the null hypothesis that there is not much difference in the personal values of Singaporean Chinese managers in the different age groups, only with the exception of the value dimension, dogmatism.